HISTORICAL, TENDENCY, MAPPING, LOOPING (H.T.M.L) FRAMEWORK FOR MANAGERIAL CAPABILITIES: AN EXPLORATORY STUDY - Adiabagus Wijaya; Mohammad Agung Saryatmo (Graduate Program of Universitas Tarumanagara, 2024)
In a company, management is a very important process in achieving company goals. Management is dynamic/not static, not rigid, but follows developments and progress in the environment that influences it. Basically, management is a series of activities that include the processes of planning, organizing, leading and controlling the efforts of organizational members in using all organizational resources to achieve predetermined goals. However, a manager needs several frameworks that must be understood so that management systems and patterns in formulating a strategy have a positive impact on organizational growth. The H.T.M.L framework, which includes the Historical, Tendency, Mapping, Looping process, is one of the managerial abilities in management practices in organizations. This research uses a qualitative approach with an exploratory study : literature review, which was carried out as an initial study in the Historical, Tendency, Mapping and Looping framework research or known as the H.T.M.L framework. The journals used in this review are various international journals obtained from several reputable journal databases. After going through a screening process using several inclusion and exclusion criterias, an analysis was carried out based on the selected journals that are related to answering the research question. Next, researchers will form a framework that can be used as a comprehensive guidance in designing and developing strategies and initiatives in organizations. This research provides results that the H.T.M.L (Historical, Tendency, Mapping, and Looping) framework can be used to facilitate the process regarding the details of how to develop and implement strategies. Through this framework, managerial capability in optimizing the success of a strategic practice can be described and explained using clear methods and pathways.